GE_GERICHTE P/7060/2016 vom 27. April 2021 - GE Cour de justice (2021)
COMPÉTENCE RATIONE LOCI;ESCROQUERIE;ABUS DE CONFIANCE;LIEU DE RÉSULTAT; LIEU DE COMISSION | CPP.319.alal; CP.3; CP.8; CP.146; CP.138